Oriented electron transmission in polyoxometalate-metalloporphyrin organic framework for highly selective electroreduction of CO2. Issue 1 (December 2018) - Wang, Yi-Rong; Huang, Qing; He, Chun-Ting; Chen, Yifa; Liu, Jiang; Shen, Feng-Cui; Lan, Ya-Qian
Abstract The design of highly stable, selective and efficient electrocatalysts for CO2 reduction reaction is desirable while largely unmet. In this work, a series of precisely designed polyoxometalate-metalloporphyrin organic frameworks are developed. Noted that the integration of ε-PMo8 V Mo4 VI O40 Zn4 cluster and metalloporphyrin endows these polyoxometalate-metalloporphyrin organic frameworks greatly advantages in terms of electron collecting and donating, electron migration and electrocatalytic active component in the CO2 reduction reaction. Thus-obtained catalysts finally present excellent performances and the mechanisms of catalysis processes are discussed and revealed by density functional theory calculations. Most importantly, Co-PMOF exhibits remarkable faradaic efficiency ( > 94%) over a wide potential range (−0.8 to −1.0 V). Its best faradaic efficiency can reach up to 99% (highest in reported metal-organic frameworks) and it exhibits a high turnover frequency of 1656 h−1 and excellent catalysis stability ( > 36 h). While CO2 reduction provides a way to remove carbon from the atmosphere, it is challenging to design effective, selective materials for this process. Here, authors construct metal-organic frameworks from polyoxometalates and porphryins to direct electron flow and improve CO2 reduction efficiencies.